Crossing Thresholds: Some Philosophical Insights into Fish Farming - Ooms , Nicole (Recent Research Advances in Arts and Social Studies Vol. 2, 2023)
This chapter seeks to analyze from a metaphysical point of view some of the consequences that could have, for a fisherman, the fact of becoming a fish farmer. Methodologically speaking, the instruments are typical of philosophy: analysis of concepts –here mainly related to space, time and movement-, formulation of hypotheses and construction of arguments. The possibility that the fishermen have of transforming themselves into fish farmers is, in the present case, mainly the result of the work of marine biologists who, based on research on local soils, waters, fauna and flora, have also developed techniques for the practice of fish farming. For coastal regions like the southern Gulf of Mexico, and specially the port of Sisal, in which there are currently conditions for fishermen to train in the culture of octopus, snook and shrimp, the issue is of utmost importance. Last but not least, the numerous contrasts between fishing and fish farming when viewed in terms of personal and social identity point at priorities that go far beyond survival and sketch what we could call, after Gaston Bachelard, thresholds of heroism. This the reason why the present text also has a phenomenological touch.